The use of biomimicry in interiors with a focus on the South African residential industry - Morezzi, Alexia (The IIE, 2022)
The main point of this research paper is to see whether or not biomimicry is being used in interiors with a focus on the South African residential industry and what the benefits of biomimicry are using specifically a qualitative methodology approach. The problem is that it isn’t being used enough in residential design, specifically in a South African context. The researcher has decided that the only solutions to solving this problem is by educating both homeowners and people within the building industry on the advantages and disadvantages of biomimicry and showing how it can be implemented and what benefits it will have, not only for the user but the environment for years to come. The key discoveries were that biomimicry has been used for a long time but not as effectively as one would hope, everyone needs to understand that it can be more functional and not just simply mimicking nature. As of yet there isn’t any large implications that have been discovered but the researcher hopes that this study will show people the importance and beauty that is biomimicry and how using it can really have a positive input for the environment and overall well being for the user. This study hopes to help homeowners and designers to create better more regenerative buildings that will create healthier and better living spaces for users with biomimicry principles in mind.
Keywords: Interior design; Properties; Homeowners; Architecture